Transformasi Digital, Media Sosial, dan Teknologi Informasi terhadap Daya Saing UMKM Mobil Bekas Kota Batam - DESI RENATA SINURAT DESI; SURYA TJAHYADI; SYAEFUL ANAS AKLANI (JSAI (Journal Scientific and Applied Informatics), 2025)
This study aims to analyze the influence of digital transformation, social media, and information technology on the competitiveness of used car MSMEs in Batam City. A quantitative research approach was employed with a sample of 89 respondents. The results of the classical assumption tests indicate that the data are normally distributed, as shown by the Kolmogorov–Smirnov Z value of 0.068 and a significance level of 0.200 (>0.05). The multicollinearity test results show no indication of multicollinearity, with Tolerance values greater than 0.10 and VIF values below 10 (X₁ = 1.685; X₂ = 1.062; X₃ = 1.614). The heteroscedasticity test results also confirm that the model is free from heteroscedasticity, as all independent variables have significance values greater than 0.05. The simultaneous F-test shows that digital transformation, social media, and information technology collectively have a significant effect on MSME competitiveness, with an F-value of 3.264 and a significance of 0.000 (<0.05). Partial t-tests indicate that all three variables have a positive and significant influence, with a significance value of 0.000. Digital transformation has the most dominant effect (B = 0.406, t = 2.908), followed by information technology (B = 0.306, t = 2.438) and social media (B = 0.066, t = 2.518). These findings demonstrate that implementing digital transformation supported by effective utilization of social media and information technology can enhance the competitiveness of used car MSMEs in Batam City by improving operational efficiency, service innovation, and digital marketing effectiveness.